2002
DOI: 10.1128/jb.184.16.4500-4509.2002
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of the FlhB Homologue YscU of Yersinia pseudotuberculosis Is Essential for Bacterial Survival but Not for Type III Secretion

Abstract: The pathogenic species of the genus Yersinia (Yersinia pestis, Y. enterocolitica, and Y. pseudotuberculosis) cause infections of highly varied severity in humans. Y. pestis causes plague and is transmitted by flea bites or infectious aerosols, whereas Y. enterocolitica and Y. pseudotuberculosis are enteric pathogens that cause gastroenteritis after the ingestion of contaminated food or water (for reviews, see references 9 and 35). Still, the virulence mechanisms of the different species show a lot of similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
82
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 42 publications
13
82
1
4
Order By: Relevance
“…In any event, this suppression suggests that YscU, together with YscP, has a role in regulating the secretion of Yop effectors as well as YscF in the Yersinia TTSS. Like FlhB (30), the C-terminal cytoplasmic part of YscU is organized into two domains, as it was demonstrated that YscU was specifically proteolyzed in vivo (25). Although there is no evidence that the proteolysis of YscU per se is important for the function of the Yersinia TTSS, it clearly reflects the conformation of the YscU cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 99%
“…In any event, this suppression suggests that YscU, together with YscP, has a role in regulating the secretion of Yop effectors as well as YscF in the Yersinia TTSS. Like FlhB (30), the C-terminal cytoplasmic part of YscU is organized into two domains, as it was demonstrated that YscU was specifically proteolyzed in vivo (25). Although there is no evidence that the proteolysis of YscU per se is important for the function of the Yersinia TTSS, it clearly reflects the conformation of the YscU cytoplasmic domains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the structural components of the inner and outer rings of the NC (PrgH, PrgK, and InvG) (6) and the needle and inner rod proteins (PrgI and PrgJ) (17,18), we detected the export apparatus components InvA (19), SpaP, and SpaS (20) (Table S1). To validate the interaction of the export apparatus components with the NC base, we immunoprecipitated the complex from a strain carrying a carboxy terminal FLAG-epitope tagged allele of SpaS (SpaS N258A ), which carries a mutation in its catalytic, autoprocessing site, thus preventing the cleavage of its carboxyl terminus (21,22). Proteins affinity purified with an anti-FLAG antibody were separated by BN-PAGE, and the band corresponding to the NC was analyzed by LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…In Yersinia pseudotuberculosis, mutations in the cytoplasmic domain of the inner membrane protein YscU (FlhB homologue) suppress the yscP (fliK homologue) polyneedle phenotype (39). In addition, it has been shown that specific cleavage occurs at the equivalent site (Asn-263/Pro-264) of YscU, and mutations at this site have complex effects on late substrate secretion and growth (40).…”
Section: Discussionmentioning
confidence: 99%